Marketing and corporate profitability: the case of Greek firms - Panigyrakis, George G.; Kapareliotis, Ilias; Ventoura, Zoe (My University, 2009)
Purpose – The purpose of this paper is to investigate the contribution of marketing and research and development (R&D) strategies to the profitability of Greek companies. Design/methodology/approach – With the use of secondary data the current research uses variables related to advertising and branding and also R&D expenses for Greek companies. Findings – Results show that there is no significant relationship between R&D intensity and profitability. R&D is not a leading factor to profitability, despite what the literature review supports. Originality/value – Different variables contribute to a company's profitability. There is little research related to the impact of corporate profitability and marketing. The present study is a first attempt to measure the impact of marketing activities and the corporate profitability on the Greek business environment.
Keywords: Greece; Marketing strategy; Profit maximization; Research and development